Update Breast Cancer 2024 Part 2-Patients with Early Stage Breast Cancer Update Mammakarzinom 2024 Teil 2 – Patientinnen mit Frühstadien des Mammakarzinoms - Janni, Wolfgang; Kolberg, Hans Christian; Hartkopf, Andreas D.; Fehm, Tanja N.; Welslau, Manfred; Müller, Volkmar; Schütz, Florian; Fasching, Peter; Jackisch, Christian; Marme, Frederik; Hörner, Manuel; Keller, Katharina; et al. (Geburtshilfe und Frauenheilkunde, 2025)
This review summarizes the latest developments for the treatment of patients with early-stage breast cancer. Most of the clinically relevant changes were the result of using immune checkpoint inhibitors to treat patients with triple-negative breast cancer (TNBC) and CDK4/6 inhibitors to treat patients with hormone receptor-positive, HER2-negative (HRpos/HER2neg) tumors and a high risk of recurrence. Recent studies are presenting more and more data with long follow-up times and integrating translational analyses to evaluate new biomarkers such as circulating tumor DNA (ctDNA). This review article summarizes the latest developments published in recent months and puts the findings in context.
CRIS-Team Scopus Importer:2025-05-30
Keywords: biomarker; breast cancer; clinical studies; early breast cancer